A comparative review on neuroethical issues in neuroscientific and neuroethical journals - Ishida, Shu; Nishitsutsumi, Yu; Kashioka, Hideki; Taguchi, Takahisa; Shineha, Ryuma (Frontiers in Neuroscience, 2023)
This study is a pilot literature review that compares the interest of neuroethicists and neuroscientists. It aims to determine whether there is a significant gap between the neuroethical issues addressed in philosophical neuroethics journals and neuroscience journals. We retrieved 614 articles from two specialist neuroethics journals (Neuroethics and AJOB Neuroscience) and 82 neuroethics-focused articles from three specialist neuroscience journals (Neuron, Nature Neuroscience, and Nature Reviews Neuroscience). We classified these articles in light of the neuroethical issue in question before we compared the neuroethical issues addressed in philosophical neuroethics with those addressed by neuroscientists. A notable result is a parallelism between them as a general tendency. Neuroscientific articles cover most neuroethical issues discussed by philosophical ethicists and vice versa. Subsequently, there are notable discrepancies between the two bodies of neuroethics literature. For instance, theoretical questions, such as the ethics of moral enhancement and the philosophical implications of neuroscientific findings on our conception of personhood, are more intensely discussed in philosophical-neuroethical articles. Conversely, neuroscientific articles tend to emphasize practical questions, such as how to successfully integrate ethical perspectives into scientific research projects and justifiable practices of animal-involving neuroscientific research. These observations will help us settle the common starting point of the attempt at “ethics integration” in emerging neuroscience, contributing to better governance design and neuroethical practice.